The Granuloma in Tuberculosis: Dynamics of a Host–Pathogen Collusion - Ehlers, Stefan; Schaible, Ulrich E. (Frontiers in Immunology, 2013)
A granuloma is defined as an inflammatory mononuclear cell infiltrate that, while capable of limiting growth of Mycobacterium tuberculosis, also provides a survival niche from which the bacteria may disseminate. The tuberculosis lesion is highly dynamic and shaped by both, immune response elements and the pathogen. In the granuloma, M. tuberculosis switches to a non-replicating but energy-generating life style whose detailed molecular characterization can identify novel targets for chemotherapy. To secure transmission to a new host, M. tuberculosis has evolved to drive T cell immunity to the point that necrotizing granulomas leak into bronchial cavities to facilitate expectoration of bacilli. From an evolutionary perspective it is therefore questionable whether vaccination and immunity enhancing strategies that merely mimic the natural immune response directed against M. tuberculosis infection can overcome pulmonary tuberculosis in the adult population. Juxtaposition of molecular pathology and immunology with microbial physiology and the use of novel imaging approaches afford an integrative view of the granuloma’s contribution to the life cycle of M. tuberculosis. This review revisits the different input of innate and adaptive immunity in granuloma biogenesis, with a focus on the co-evolutionary forces that redirect immune responses also to the benefit of the pathogen, i.e. its survival, propagation and transmission.